Excellent Survival Regardless of Disease Stage in Patients with Advanced Nasopharyngeal Cancer. Issue 4 (July 2016) - Belgioia, Liliana; Bacigalupo, Almalina; Vecchio, Stefania; Marcenaro, Michela; Pupillo, Francesco; Agostinelli, Stefano; Corvò, Renzo
Background: We present our experience in assessing the feasibility and efficacy outcomes of intensified intensity-modulated radiation therapy (IMRT) with simultaneous integrated boost (SIB) delivered to patients with nasopharyngeal carcinoma (NPC). Methods: Between March 2009 and December 2014, 35 patients affected by advanced NPC with a median age of 53 years (range 11-77) were treated with definitive radiotherapy. Radiotherapy was delivered by helical tomotherapy with the SIB technique. The prescribed doses were 66 Gy to macroscopic disease, 60 Gy to high-risk subclinical disease, and 54 Gy to low-risk disease in 30 fractions. The daily SIB dose was 2.2 Gy to macroscopic disease. Results: At the end of treatment 33 (94%) patients had obtained complete clearance of disease and 2 patients had died (1 of persistent disease after 3 months and 1 of cancer-unrelated causes after 4 months). At a median follow-up of 40 months (range 5-69), locoregional control rates at 2 and 4 years were 92.9% and 88.2%, respectively, and the overall survival after 4 years was 93.9%. The most significant acute toxicities were grade 2 and 3 mucositis (43%). No grade 3 and 4 late toxicities were observed; grade 2 xerostomia after 6 months from the end of treatment was reported in 11 patients; xerostomia toxicity decreased to grade 1 in 6/11 patients within 12 months. Conclusions: These results show that intensified IMRT with SIB is an excellent strategy offering high local control rates for NPC patients with mild acute and late toxicity.